SAT0625-HPR FATIGUE AND CONTRIBUTING FACTORS IN CHINESE PATIENTS WITH ANKYLOSING SPONDYLITIS. (2nd June 2020) - Zhou, W.; Guo, J.; Zhao, R.; Dong, C.; Gu, Z.
Abstract : Background: Ankylosing spondylitis (AS) is a systemic chronic inflammatory disease, which most likely occurs in young men. It mainly affects sacroiliac joints, axial skeleton, thoracic cage and seriously decreasing quality of life in AS patients[1, 2]. In recent years, fatigue of AS patients has been paid more and more attention[3]. Fatigue is a complex feeling, diseased individuals describe fatigue as a sense of tiredness at rest, exhaustion with activity, lack of energy which affects daily work, inertia or lack of endurance, or as loss of vitality. It has been confirmed that fatigue is not only a symptom but may also be quantified by fatigue scores and can be modified by various measures depending on the underlying cause[4]. However, there has been no study about fatigue in AS patients in China. Objectives: This study aimed to evaluate the predictors of fatigue and the effects of fatigue on HR-QoL among patients with AS. Methods: A total of 150 AS patients were involved in the study. A series of questionnaires included: Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Metrology Index (BASMI), Bath Ankylosing Spondylitis Functional Index (BASFI), the 10 cm Visual Analog Scale (VAS), the Self-Rating Anxiety Scale (SAS), the Self-Rating Depression Scale (SDS), the Pittsburgh Sleep Quality Index (PSQI), the Health Assessment Questionnaire-Disability Index (HAQ-DI), the Short Form 36 Health Survey (SF-36) and the Fatigue Severity Scale(FSS). Independent samples t-test, Mann–Whitney U-test, Chi-square analysis, Pearson /Spearman correlation and binary logistic regression were used to analyze the data. Results: The results demonstrated that 48.7% individuals with AS suffered from fatigue. Compared with AS patients without fatigue, AS patients with fatigue showed higher WHR( P <0.05), increased BASDAI ( P <0.01) and poorer BASFI ( P <0.05). Meanwhile, AS patients with fatigue tended to have more severe pain( P <0.05), higher degree of anxiety( P =0.001), more serious functional disability( P =0.001) and worse sleep quality( P =0.001). Binary logistic regression indicated that WHR (OR=1.78, P <0.05), BASDAI (OR=1.34, P =0.01), sleep disturbance (OR=2.35, P <0.05) were independent predictors of fatigue in AS patients. Additionally, the occurrence of fatigue significantly reduced the quality of life in AS patients both physically and psychologically. Conclusion: These findings suggested that medical personnel should pay more attention to AS patients with fatigue and take effective measures to relieve fatigue. References: [1]Law L, Beckman Rehnman J, Deminger A, Klingberg E, Jacobsson LTH, Forsblad-d'Elia H (2018) Factors related to health-related quality of life in ankylosing spondylitis, overall and stratified by sex. Arthritis research & therapy 20 (1):284. doi:10.1186/s13075-018-1784-8 [2]Hanson A, Brown MA (2017) Genetics and the Causes of Ankylosing Spondylitis. Rheumatic diseases clinics of North America 43 (3):401-414. doi:10.1016/j.rdc.2017.04.006 [3]Ulus Y, Akyol Y, Bilgici A, Kuru O (2019) Association of work instability with fatigue and emotional status in patients with ankylosing spondylitis: comparison with healthy controls. Clinical rheumatology 38 (4):1017-1024. doi:10.1007/s10067-018-4366-x [4]Finsterer J, Mahjoub SZ (2014) Fatigue in healthy and diseased individuals. The American journal of hospice & palliative care 31 (5):562-575. doi:10.1177/1049909113494748 Acknowledgments: Thanks to all the authors for their efforts and thanks to all members of the Department of Rheumatology of Affiliated Hospital of Nantong University for their helpfulness in the acquisition of data. Disclosure of Interests: None declared